Building a Tailored, Multilevel Prevention Strategy to Support Children and Families Affected by Parental Incarceration. (2nd January 2017) - Kjellstrand, Jean
ABSTRACT: During the past several decades, a wave of incarceration engulfed the United States. In the wake of this "mass incarceration" are children and families who continue to struggle from its impact. Although findings are now emerging on the impacts of incarceration, there are few studies that have examined how to best intervene to promote positive development for those children who have had a parent incarcerated. While there are common risks and challenges faced by children and their families, the significant variation between and among these individuals and their relationships highlights the challenges in finding solutions. Given the number of issues at play, it is clear that a "one-size-fits-all" approach to addressing child needs is not sufficient. This article examines some of the common challenges faced by families impacted by parental incarceration as well as existing interventions designed to help support children and families overcome these challenges. It then offers some potential directions for the field to move, to develop a prevention strategy that meets the needs within the population and leads to better outcomes for the children of incarcerated parents, their families, and their communities.